Analisis Pola Komunikasi Organisasi Karyawan di Divisi Humas PT PLN (PERSERO) Unit Induk Distribusi SULSELBAR Makassar - Riyadi, Ilham; Aqifah, Rifka; Muhtadiah, Dian (Kybernology : Journal of Government Studies, 2025)
Organizational communication plays a crucial role in facilitating work coordination and ensuring effective interactions among employees. This study aims to analyze the organizational communication patterns applied in the Public Relations Division of PT PLN (Persero) Sulselbar Distribution Main Unit. Using a qualitative descriptive approach, data were collected through observations and interviews with employees in the division. The findings reveal that organizational communication in this division follows three main patterns: wheel, chain, and circle. Although these communication patterns help streamline coordination, several obstacles hinder optimal communication, including technical limitations, semantic misunderstandings, and human-related factors that affect the effectiveness of information delivery. Therefore, this study recommends improvements in internal communication systems, such as establishing clearer communication channels, enhancing openness in employee interactions, and optimizing feedback mechanisms. By understanding the implemented communication patterns and identifying existing barriers, this study provides valuable insights for the company to develop more effective and efficient organizational communication strategies.